MSME Loan Composition, Financial Stability, and Government Ownership: Evidence from Indonesia’s Banking Sector - Muhammad, Nur; Lubis, Arief Wibisono (Gadjah Mada International Journal of Business, 2025)
The Indonesian government has promoted growth in MSMEs (micro, small, and medium enterprises) by targeting banks to allocate at least 30% by Q2 2022 of their loan portfolios to MSMEs. However, by Q4 2022, this target had not been met, partly due to the high credit risk and information asymmetry in the MSME sector. While past studies often suggest that MSME lending improves bank stability, this study finds otherwise. Using panel data from 96 banks between Q1 2019 and Q4 2022 and applying the GMM method, the result shows that a higher MSME loan share tends to reduce bank stability. Interestingly, when government ownership is considered, the effect turns positive, suggesting that government-owned banks may manage MSME risks better. This may be due to stronger oversight, policy support, their experience with development-focused lending, a broader business focus beyond profits, and their role as agents of change in supporting financial inclusion and economic stability. These findings suggest the need for better MSME policy alignment, risk mitigation tools, and a centralized MSME database to balance financial inclusion with banking sector stability.